Substituting a value-added tax for the corporate income tax : first-round analysis - Dresch, Stephen P.; Lin, An-loh; Stout, David K. (Cambridge, Mass. : Ballinger Pub. Co., 1977)
This book is divide into two basic parts: identification of probable first -round price changes resulting from the tax substitution and discussion of the potential implications of these for such substantive issues as income distribution, international trade, etc..
Includes index.
Bibliography: p. 199-200.
obn 22/01/2019
Loans
Keywords: Value-added tax; Corporations; Prices; Income distribution